Chemical characters of disease suppressive and conducive soil of Moler on shallot in Brebes Central Java. Issue 1 (November 2021) - Poromarto, S H; Supyani,; Supriyadi,; Hadiwiyono,
Abstract: In the latest years, a disease epidemy of Moler caused by Fusarium oxysporum f.sp. cepae have just occurred in Brebes Central Java. The disease intensity, however, varies between the shallot production lands. Some lands show suppressive with disease intensity lower than 5%, and others are conducive to disease intensity over 50%. It is interesting that in Brebes occur suppressive and conducive soil to moler disease. The suppressiveness may be determined by environmental conditions, including chemical soil characters. This paper reports the chemical character of suppressive and conducive soil to moler disease in Brebes. The evidence shows that the suppressive soil is more fertile than that conducive one. The suppressive soil is chemically characterized by significantly higher organic mineral, C-organic, P-available, K-exchangeable, and Cation Exchange Capacity than that conducive one.